Compression-Induced Solidification: A Novel Processing Technique for Precise Thermoplastic Optical Components with Negligible Internal Stresses - Jungmeier, Ariane; Wildner, Wolfgang; Drummer, Dietmar; Kühnert, Ines (ISRN Optics, 2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KT.compre

Dickwandige Kunststoffoptiken - Druckverfestigung als neues Verfahren für präzise Bauteile - Jungmeier, Ariane; Drummer, Dietmar; Kühnert, Ines (Kunststoffe in Optischen Systemen, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KT.dickwa

Influence of a locally variable mold temperature on injection molded thin-wall components - Fischer, Christopher; Jungmeier, Ariane; Peters, Guido; Drummer, Dietmar (Journal of Polymer Engineering, 2018)

Long-Term Properties of Injection-Molded Micro-Parts: Influence of Part Dimensions and Cooling Conditions on Aging Behavior - Meister, Steve; Jungmeier, Ariane; Drummer, Dietmar (Macromolecular Materials and Engineering, 2013)
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-KT.longte

Microthermoforming Integrated in the Injection Molding Process for Fabrication of Film-Based Microstructured Parts - Jungmeier, Ariane; Drummer, Dietmar (International Polymer Processing, 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KT.microt

Mikrothermoformen thermoplastischer Folien im Spritzgießprozess - Jungmeier, Ariane; Drummer, Dietmar (7. Kolloquium Mikroproduktion, 2015)
UnivIS-Import:2016-06-01:Pub.2015.tech.FT.FT-KT.mikrot

Neuartiges Werkzeug- und Temperierkonzept für tribologisch optimierte Mikroteile - Drummer, Dietmar; Jungmeier, Ariane; Leisen, Christoph; Peters, Guido (Konstruktion, 2014)
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.FT-KT.neuart

New Aspects of Process-Induced Properties of Micro Injection Molded Parts - Jungmeier, Ariane; Drummer, Dietmar; Ehrenstein, Gottfried (Plastics Rubber and Composites, 2010)
UnivIS-Import:2015-03-09:Pub.2010.tech.FT.FT-KT.newasp

New aspects of process induced properties of microinjection moulded parts - Jungmeier, Ariane; Ehrenstein, Gottfried; Drummer, Dietmar (Plastics Rubber and Composites, 2010)
Keywords: Cooling rate; Mechanical properties; Microinjection moulding; Morphology; Thermoplastics

Novel mold and tempering concept for tribological optimized micropartsnovel mold and tempering concept for tribological optimized microparts Neuartiges Werkzeug- und Temperierkonzept fur tribologisch optimierte Mikroteile - Drummer, Dietmar; Leisen, Christoph; Jungmeier, Ariane; Peters, Guido (Konstruktion, 2014)

Optimierungsstrategien für Mikrobauteile - Jungmeier, Ariane; Drummer, Dietmar (Kunststoffe, 2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.FT.FT-KT.optimi

Optimization Strategies for Micro Parts - Jungmeier, Ariane; Drummer, Dietmar (Kunststoffe International, 2011)
Technical micro parts are negatively affected by the flow and cooling conditions experienced during injection molding in comparison to macro parts. With the cooling dependent low degree of crystallization in the core and the high flow dependent component in the boundary layers combined with the high levels of orientation there is a high degree of inhomogeneity across the part and thus sub-optimal conditions for the in-service properties in general. An option for optimizing micro parts is processing using low thermal conductive mold inserts, which also leads to a reduced cooling rate. By manufacturing with inserts made from zirconium oxide with a thermal conductivity of 2 W/mK similar property values to variothermal process control can be achieved. The results show that materials with high rates of crystallization and high crystallization potential have beneficial effects on the properties of micro parts. However, possible flow dependent property anisotropy also has to be considered.
UnivIS-Import:2015-03-09:Pub.2011.tech.FT.FT-KT.optimi_4

The effect of temperature and pressure on microthermoforming thermoplastic films integrated in the injection moulding process - Jungmeier, Ariane (Journal of Polymer Engineering, 2015)
UnivIS-Import:2016-02-10:Pub.2015.tech.FT.FT-KT.theeff_7

The influence of proccessing temperature on morphological and tribological properties of injection-moulded micro parts - Fischer, Christopher; Leisen, Christoph; Merken, Daniel; Jungmeier, Ariane; Drummer, Dietmar (Advances in Mechanical Engineering, 2014)
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.FT-KT.theinf

Untersuchungen zum Mikrothermoformen von Polycarbonat-Folien und zu dessen Integration in den Spritzgießprozess - Jungmeier, Ariane; Fischer, Christopher (Zeitschrift Kunststofftechnik, 2016)
UnivIS-Import:2017-01-09:Pub.2016.tech.FT.FT-KT.unters